Solidarity economy of culture and cultural citizenship in the abc region of sao paulo, brazil. (CAMBRIDGE SCHOLARS PUBLIS, 2018)
How can artists in a developing country be able to dedicate themselves to the laborious task of creating art when there are few resources? How can the government and intellectuals support artists without imposing a centralized idea of national culture? This book explores these questions and others, focusing on lived experience in the ABC region of São Paulo, Brazil. Beginning with two lectures by two renowned professors and activists of the Brazilian solidarity movement, Ladislau Dowbor and Célio Turino de Almeida, the book then opens up space for artists from diverse areas to speak about thei.